2019
DOI: 10.1038/s41598-019-44973-y
|View full text |Cite
|
Sign up to set email alerts
|

The purinergic receptor antagonist oxidized adenosine triphosphate suppresses immune-mediated corneal allograft rejection

Abstract: Adenosine triphosphate (ATP) is released into the extracellular environment during transplantation, and acts via purinergic receptors to amplify the alloimmune response. Here, using a well-established murine model of allogeneic corneal transplantation, we investigated the immunomodulatory mechanisms of the purinergic receptor antagonist oxidized ATP (oATP). Corneal transplantation was performed using C57BL/6 donors and BALB/c hosts. oATP or sterile saline was administered via intraperitoneal injection for 2 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
2
3
0
Order By: Relevance
“…17,[27][28][29][30]48,49 Consistent with these studies, we found that increased eATP also exacerbated corneal allograft rejection via the P2X7 receptor. Pharmacological blockade of ATP/P2X7 signaling not only reduced corneal allograft rejection, in line with results by Foulsham et al, 50 but also significantly blunted the NLRP3 inflammasome-mediated maturation and release of IL-1β. However, further studies are needed to explore the mechanism that regulates the release of ATP, which remains largely unknown in our pathological scenarios.…”
Section: Blockade Of the Il-6/il-1β-stat3 Signaling Pathway Prolongsupporting
confidence: 87%
“…17,[27][28][29][30]48,49 Consistent with these studies, we found that increased eATP also exacerbated corneal allograft rejection via the P2X7 receptor. Pharmacological blockade of ATP/P2X7 signaling not only reduced corneal allograft rejection, in line with results by Foulsham et al, 50 but also significantly blunted the NLRP3 inflammasome-mediated maturation and release of IL-1β. However, further studies are needed to explore the mechanism that regulates the release of ATP, which remains largely unknown in our pathological scenarios.…”
Section: Blockade Of the Il-6/il-1β-stat3 Signaling Pathway Prolongsupporting
confidence: 87%
“…As ATP can be released during damage elicited by ischemia and reperfusion, the P2X4-ATP pathway likely contributes to the recruitment and activation of naı ¨ve T cells into the graft. Another study on this topic revealed that use of a purinergic receptor antagonist, oxidized ATP, results in diminished IFNg-secreting T H 1 CD4 þ T cells and prolonged graft survival in a murine corneal transplant model [2]. These data suggest that extracellular ATP plays an important role in the activation of alloreactive T cells, whether through decreased maturation of CD11b þ APCs as this group showed, or through T-cell intrinsic immunomodulatory mechanisms that have been reported by others [3,4].…”
Section: Danger-associated Molecular Patterns Directly Signal On T Cellssupporting
confidence: 70%
“…In the current study, we show that epithelium‐derived IL36γ promotes the migration of immune cells to the injured tissue, as indicated by a significant 34% reduction in the frequencies of total CD45 + leukocytes in corneas treated with IL36RA. Previous studies have shown that corneal immune microenvironment is dependent not only on the frequencies, but also specific immune cell subsets 32,33 . Our detailed analysis of immune cell subsets demonstrates IL36RA treatment results in approximately 47% and 24% reduction in the frequencies of neutrophils and macrophages, respectively, at the ocular surface.…”
Section: Discussionmentioning
confidence: 58%
“…Previous studies have shown that corneal immune microenvironment is dependent not only on the frequencies, but also specific immune cell subsets. 32,33 Our detailed analysis of immune cell subsets demonstrates IL36RA treatment results in approximately 47% and 24% reduction in the frequencies of neutrophils and macrophages, respectively, at the ocular surface. Moreover, we show that IL36γ promotes the activation of immune cells at the ocular surfaces, as evidenced by the significant decrease in the expression of IL1β and TNFα following in vivo administration of IL36Ra to mouse corneas.…”
Section: Discussionmentioning
confidence: 87%